APPLICATION OF STAD-TYPE COOPERATIVE LEARNING MODEL TO INCREASE STUDENT LEARNING OUTCOMES - Ramdhani, Fahmy Febi; Sukrawan, Yusep; Permana, Tatang (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2022)
This study aims to implement a cooperative learning model of the Student Teams Achievement Division (STAD) type in improving student learning outcomes in the Basic Automotive Engineering (PDTO) subject of Motorcycle Engineering and Business Department at Setia Bhakti Vocational School, Cilawu Garut for the 2022/2023 academic year. This Classroom Action Research (CAR) uses the Kemmis and Taggart research model. The research flow consists of (1) Planning, (2) Action, (3) Observation, (4) Reflection. The subjects of this study were students of class X TBSM SMK Setia Bhakti, Cilawu Garut, totaling 25 students. The research data were obtained using student activity observation sheets, interviews with PDTO subject teachers and with learning outcomes tests. The technique used to analyze the data is a qualitative descriptive technique. The results of this study indicate an increase in the percentage of completeness of PDTO learning outcomes for students of class X TBSM SMK Setia Bhakti in each cycle. In Cycle I, the percentage of students' learning completeness was 56% with an average grade of 74.48. In the second cycle the percentage of students' learning completeness reached 93.75% with an average grade of 89.14.